2022
DOI: 10.1002/tafs.10360
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Foodscape for Stream‐Dwelling Cutthroat Trout Reveals Spatial and Temporal Ranges of Resource Exploitation and Energy Intake

Abstract: Food availability is a primary factor limiting the abundance of wild populations, but quantifying it requires an understanding of when and where prey are vulnerable to predators. Salmonid fishes in streams are commonly thought to forage on drifting aquatic invertebrates during daylight hours. However, past studies also report benthic and nocturnal foraging despite the predominant view of salmonids as diurnal drift‐feeding predators. We used instream videography to assess foraging mode and energy intake for str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Heggenes et al (1991) reported that cutthroat trout larger than 9 cm total length selected stream habitats with depths >25 cm, and maximum channel depths are already or projected to be below this threshold in many study streams. Finally, slower velocity would reduce drift food availability, which is the primary food source for stream salmonids in summer (Owens & Keeley, 2022; Uthe et al, 2019). Optimal foraging velocity of stream salmonids during base flow conditions range between 20 and 40 cm/s (Morita, Sahashi, & Tsuboi, 2016; Nislow, Folt, & Parrish, 1999), which again fall within the velocity range projected in the current and future climate scenarios for the study sites.…”
Section: Discussionmentioning
confidence: 99%
“…Heggenes et al (1991) reported that cutthroat trout larger than 9 cm total length selected stream habitats with depths >25 cm, and maximum channel depths are already or projected to be below this threshold in many study streams. Finally, slower velocity would reduce drift food availability, which is the primary food source for stream salmonids in summer (Owens & Keeley, 2022; Uthe et al, 2019). Optimal foraging velocity of stream salmonids during base flow conditions range between 20 and 40 cm/s (Morita, Sahashi, & Tsuboi, 2016; Nislow, Folt, & Parrish, 1999), which again fall within the velocity range projected in the current and future climate scenarios for the study sites.…”
Section: Discussionmentioning
confidence: 99%
“…Foodscapes, though developed for herbivores navigating immobile forage [49,55], can also be extended further up the food chain, as prey resource selection will shape the movements and selected hunting strategies of their predators [56].…”
Section: Energetic Landscapes Reveal Foraging Costsmentioning
confidence: 99%
“…These dynamics become more complicated in multi-predator systems where prey must contend with predators using different hunting strategies, resulting in complex landscapes of fear with varying levels of risk [ 52 ]. The concept of foodscapes, though developed for herbivores navigating immobile foraging resources [ 46 , 53 ], can also be extended further up the food chain, as prey resource selection will shape the movements and selected hunting strategies of their predators [ 54 ]. The landscape of disgust arises from parasite avoidance behaviour, with further consequences for predator–prey interactions and scavenging decisions [ 48 , 55 ].…”
Section: Introductionmentioning
confidence: 99%